1989
DOI: 10.1007/bf00145037
|View full text |Cite
|
Sign up to set email alerts
|

Prospective follow-up of cervical HPV infections: Life table analysis of histopathological, cytological and colposcopic data

Abstract: A total of 532 women with established cervical HPV infection have been prospectively followed (without treatment) since 1981 for a mean of 45 (SD 21) months. The patients were examined by colposcopy, PAP smears and/or punch biopsy every 6 months. The life-table method was applied to analyze the clinical course (i.e. regression and progression) of the HPV lesions, stratified by their colposcopic pattern, PAP smear findings and grade of CIN. During the follow-up, 107 (41.8%) of 256 patients with HPV-NCIN lesion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
37
0
3

Year Published

1990
1990
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(42 citation statements)
references
References 30 publications
2
37
0
3
Order By: Relevance
“…Our mean follow-up time was 17.3 + 3.1 years, which is considerably longer than that of any prospective studies (Koss et al 1963;Nasiell et al 1986;Syrj~nen et al 1988;Kataja et al 1989aKataja et al , 1989b. Forty-nine lesions (23.9%) showed no histological evidence of HPV infection (Kadish et al 1986;Koss 1987;Meisels et al 1976;Syrjfinen 1983) (Table 1).…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Our mean follow-up time was 17.3 + 3.1 years, which is considerably longer than that of any prospective studies (Koss et al 1963;Nasiell et al 1986;Syrj~nen et al 1988;Kataja et al 1989aKataja et al , 1989b. Forty-nine lesions (23.9%) showed no histological evidence of HPV infection (Kadish et al 1986;Koss 1987;Meisels et al 1976;Syrjfinen 1983) (Table 1).…”
Section: Discussionmentioning
confidence: 72%
“…While HPV DNA negativity, HPV6 and HPVll occur commonly in low grade lesions, the grade of the lesion at first biopsy seems to be directly related to clinical course (Table 6). Because of its predictive value, an accurate histological grading of lesions is mandatory (Syrjfinen 1987;Kadish et al 1986;Kataja et al 1989a;Murdoch et al 1988;Syrjfinen et al 1987.…”
Section: Discussionmentioning
confidence: 99%
“…There are 58 HPV types recognized to date. More than 10 HPV types, (HPV 6,11,16,18,31,33,35,39,42,etc. ) have been demonstrated in the genital tract.…”
Section: Introductionmentioning
confidence: 99%
“…The data collected during these years suggest that the natural course of cervical HPV infections is equivalent to that of CIN (28,32,36). In our recent report (11) we used survival analysis to assess the factors associated with either benign or aggressive behavior of the cervical HPV infections. The clinical course of HPV infection was markedly influenced by the grade of the lesion in the first biopsy, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, Kataja et al also reported that 20% of HPV-positive CIN2 progressed to CIN3 over a mean followup period of 45 months. 9 Therefore, it is crucial to elucidate whether or not HPV genotyping is useful to screen patients with CIN2 for higher progression risk who would benefit from more intensive follow-up or therapeutic intervention. In Japan, this is of concern because the incidence of carcinoma in situ (CIS) and that of invasive cervical cancer are rapidly increasing among women aged 39 years.…”
mentioning
confidence: 99%